Digital Language Learning through Instructional design by using Tubequizard in EFL Classroom - Muthmainnah Muthmainnah; Besse Darmawati; Umar Sidik; Saidna Zulfikar Bin Tahir; Ahmad Al Yakin; Hasan Hasan (Makassar State University, 2023)
Abstract. In today's information technology-integrated education, designing teaching activities for digital learning and flexibly using technology tools is the most important issue. The design of authentic materials and materials in English as a second or foreign language via Tubequizard's innovative web has a significant impact on language learners at the university level, according to this paper. Applying a mixed method, this study highlighted the undergraduate students’ perceptions of their experience with Tubequizard as ELT materials during COVID 19. By using purposive sampling, this study sample involved 71 students and five students for an online interview at the computer science faculty of Universitas Al Asyariah Mandar located at West Sulawesi, Indonesia. By conducting an online survey, the instruments of this study used a questionnaire and interviews. The findings of this study resulted in Tubequizard content being helpful to students to engage and motivate them in learning English, and their respondents strongly believe that Tubequizard is a technology innovation for lecturers in designing their teaching materials to be more interesting, easy to understand, Tubequizard materials according to the student’s needs, supported accelerate learning, suitable for all English skills, engage students in active and autonomous learning, expand students’ knowledge, meet positively students expectations in English class, encourage students to think creatively and critically, and suitable to give ideas for EFL classroom than the traditional model. Thus, it can be concluded that for teaching foreign languages, authentic and culturally appropriate materials are essential.Keywords: Digital language learning, developing materials, EFL, Technology and Tubequizard